IL-6 Production by Dendritic Cells Is Dispensable for CD8+ Memory T-Cell Generation. (30th December 2012) - Daudelin, Jean-François; Mathieu, Mélissa; Boulet, Salix; Labrecque, Nathalie
Abstract : Following activation, naïve CD8 + T cells will differentiate into effectors that differ in their ability to survive: some will persist as memory cells while the majority will die by apoptosis. Signals given by antigen-presenting cells (APCs) at the time of priming modulate this differential outcome. We have recently shown that, in opposition to dendritic cell (DC), CD40-activated B-(CD40-B) cell vaccination fails to efficiently produce CD8 + memory T cells. Understanding why CD40-B-cell vaccination does not lead to the generation of functional long-lived memory cells is essential to define the signals that should be provided to naïve T cells by APCs. Here we show that CD40-B cells produce very low amount of IL-6 when compared to DCs. However, supplementation with IL-6 during CD40-B-cell vaccination did not improve memory generation. Furthermore, IL-6-deficient DCs maintained the capacity to promote the formation of functional CD8 + effectors and memory cells. Our results suggest that in APC vaccination models, IL-6 provided by the APCs is dispensable for proper CD8 + T-cell memory generation.